Hidradenitis suppurativa: Clinical characteristics and determinants of treatment efficacy. Issue 5 (11th July 2019) - Vural, Secil; Gündoğdu, Mustafa; Akay, Bengu N.; Boyvat, Ayşe; Erdem, Cengizhan; Koçyiğit, Pelin; Bostancı, Seher; Sanli, Hatice; Kundakci, Nihal
Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disorder that causes a significant decline in quality of life. There are numerous treatment options; however, real‐life data on the efficacy of these treatments is limited. This study was performed in two centers to describe clinical characteristics and assess treatment outcome in a cohort of 139 patients with HS. Data on demographic and clinical characteristics, Hurley stage and comorbidities were collected from patient charts and evaluated retrospectively. Treatment response was measured with HS clinical response index (HISCR). Mean body mass index was 27.8±4.88. Inflammatory comorbidities were present in 23%. Among first‐line drugs systemic doxycycline resulted in 60% HISCR followed by rifampicin–clindamycin combination (46.4%). Isotretinoin had the lowest HISCR (30.7%) in this group. For second‐line therapies, all acitretin treated patients achieved response and patients treated with tumor necrosis factor alpha (TNF‐α) inhibitors had the highest HISCR. Currently recommended first‐line therapies have moderate efficacy in HS. Acitretin appears to be a reasonable alternative for the highly effective TNF‐α inhibitors in patients with severe and resistant HS. Overall, these results support that excessive inflammatory response play an important role in pathogenesis of HS.